2020
DOI: 10.9734/jeai/2020/v42i430505
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Variability in Three Nigerian Pepper Varieties using Gamma Irradiation

Abstract: This study was aimed at inducing mutation on three cultivars of Capsicum annuum L. to source for new and favourable genetic variations that could be exploited for better agronomic traits. The mutation was induced by exposing the seeds of Shombo, Tatase and Nsukka yellow pepper to varied dosages (0, 50, 100, 150 and 200 Gy from 60Co source) of gamma irradiation. The study was conducted in the Botanic Garden of the University of Nigeria. Seeds exposed to 50Gy produced significantly (P < 0.05) the highest numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…The drastic reduction in the germination with increase in the concentration of sodium azide may be due to the induction of chromosomal structure abnormalities in the genes of vitality. This result is in synchronization with Abu et al (2020) and Ibukun et al (2019).…”
Section: Germination Percentsupporting
confidence: 70%
See 1 more Smart Citation
“…The drastic reduction in the germination with increase in the concentration of sodium azide may be due to the induction of chromosomal structure abnormalities in the genes of vitality. This result is in synchronization with Abu et al (2020) and Ibukun et al (2019).…”
Section: Germination Percentsupporting
confidence: 70%
“…Due to presence of suspected chromosomal aberrations, a delay in flowering was investigated. Abu et al (2020) and Dahiru et al (2021) also reported similar results in maize.…”
Section: Days To 50% Floweringsupporting
confidence: 66%
“…Gamma-ray induction with a dose of 50 Gy on red chili plants of the Shombo variety can increase the productivity of red chili plants from 12,553.5 kg/ha to 21,231.39 kg/ha. In addition, gamma-ray induction with a dose of 100 Gy can increase the number of leaves of red chili plants of the Tatase variety (Nigerian local variety) from 8.53 to 16.95 (Abu et al, 2020). Based on the description above, it is expected that gamma-ray irradiation on local varieties of red chili plants can produce mutant plants that have better productivity and fruit quality than the previous plants, so it is necessary to do research related to the effect of gamma-ray irradiation on the growth and yield of local varieties of red chili plants.…”
Section: Introductionmentioning
confidence: 99%
“…Gamma rays are also being widely used as mutation techniques in an attempt to improve morphological and plant growth characteristics. For example, gamma ray irradiation was used to extend the shelf life of tomatoes (Antaryami et al, 2016) and to improve potato storage capacity (Nouani et al, 1987) as well as the morphological traits in pepper (Abu et al, 2020). This can also be of great value and benefit for the improvement of eggplant.…”
Section: Introductionmentioning
confidence: 99%